Optimal controller design for an islanded microgrid during load change. (24th September 2021) - Soreng, Bineeta; Pradhan, Raseswari
This paper emphasises on developing a Sliding-Mode-Controller using Whales-Optimisation-Algorithm named as SMC-WOA technique for optimal regulation of voltage and frequency for a Photovoltaic based Microgrid (PVMG). The proposed technique is validated by the dynamic response of the studied PVMG during operation mode and load change. Here, a voltage, a current and a droop controller are used. For ensuring the efficacy of the proposed technique such as SMC-WOA, dynamic responses of the studied system with SMC-WOA are compared with that of the Grey-Wolf-Optimisation-based-SMC (SMC-GWO) and Sine-Cosine-Algorithm-based-SMC (SMC-SCA). With proper simulation results analysis, it is found that the proposed SMC-WOA helps in yielding better results compared to those of SMC-GWO and SMC-SCA techniques in terms of faster convergence with minimum voltage, frequency overshoot and Total Harmonic Distortion (THD). The validation of the proposed technique is also tested by comparing with PI controller optimised with same WOA, GWO and SCA.